Potential screening and early diagnosis method for cancer: Tongue diagnosis - HAN, SHUWEN (Int J Oncol, 2016)
Tongue diagnosis, as a unique method of traditional Chinese medicine (TCM), was used to discriminate physiological functions and pathological conditions by observing the changes of the tongue and tongue coating. The aims of the present study were to explore a potential screening and early diagnosis method of cancer through evaluating the differences of the images of tongue and tongue coating and the microbiome on the tongue coating. The DS01-B tongue diagnostic information acquisition system was used to photograph and analyze the tongue and tongue coating. The next-generation sequencing technology was used to determine the V2-V4 hypervariable regions of 16S rDNA to investigate the microbiome on the tongue coating. Bioinformatics and statistical methods were used to analyze the microbial community structure and diversity. Comparing with the healthy people, the number of mirror-like tongue, thick tongue coating and the moisture of tongue were increased in cancers. The dominant color of the tongue in the healthy people was reddish while it was purple in the cancers. The relative abundance of Neisseria, Haemophilus, Fusobacterium and Porphyromonas in the healthy people were higher than that in the cancers. We also found 6 kinds of special microorganisms at species level in cancers. The study suggested that tongue diagnosis may provide potential screening and early diagnosis method for cancer.